Psychometric properties of the generalized anxiety disorder-7 (GAD-7) in a sample of workers - Merino-Soto, César; Angulo-Ramos, Marisol; Rovira-Millán, Lillian V.; Rosario-Hernández, Ernesto (Frontiers in Psychiatry, 2023)
Objective To evaluate the psychometric properties of the GAD-7 by obtaining evidence of internal structure (dimensionality, precision and differential functioning of items) and association with external variables. Methods A total of 2,219 protocols from three different studies conducted with Puerto Rican employees that administered the GAD-7 were selected for the current study. Item response theory modeling was used to assess internal structure, and linear association with external variables. Results The items were adapted to a graduated response model, with high similarity in the discrimination and location parameters, as well as in the precision at the level of the items and in the total score. No violation of local independence and differential item functioning was detected. The association with convergent (work-related rumination) and divergent (work engagement, sex, and age) variables were theoretically consistent. Conclusion The GAD-7 is a psychometrically robust tool for detecting individual variability in symptoms of anxiety in workers.